Codoping of epitaxial zinc oxide thin films - Ong, Junxiong. (2010)
Zinc Oxide (ZnO) thin films were intentionally codoped with Group III elements (Aluminium, Gallium and Indium) in order to investigate and understand the effects of codoping on the morphological, electrical and optical properties of Gallium-doped ZnO (GZO) films. The codoped films were grown on MgAl2O4 spinel substrates using a low temperature solution-phase method known as hydrothermal synthesis and annealed at 600°C in Nitrogen ambient to improve their crystalline quality.